Polycrystalline composite tantalum carbide coating and preparation method thereof

By introducing a CVI method of combining a porous carbide transition layer with a tantalum sol into the tantalum carbide coating, the problem of easy cracks in the high temperature environment is solved, and the tantalum carbide coating is realized. More efficient protection and lower production costs.

CN118461130BActive Publication Date: 2025-02-07SHANDONG UNIV

Patent Information

Application Number
CN202410261847.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-07
Publication Date
2025-02-07
Estimated Expiration
2044-03-07

AI Technical Summary

Technical Problem

In the prior art, tantalum carbide coatings are prone to cracks in high-temperature growth environments, resulting in thermal stress between them, which in turn leads to separation and protection failure between the coating and the substrate, and the growth rate of conventional CVD methods is slow. The high cost limits its wide application in single crystal growth.

Method used

Using the method of combining the porous carbide transition layer with the tantalum sol, tantalum carbide is deposited in the porous carbide coating by the CVI method to form a polycrystalline composite tantalum carbide coating, which increases the thickness and density of the stress buffer layer and reduces the coating. Thermal mismatch between the layer and the substrate.

Benefits of technology

It effectively avoids the cracks in the dense layer of tantalum carbide, extends the service life of the coating, reduces the cost of single crystal growth, and improves the protective effect of tantalum carbide coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118461130B_ABST
    Figure CN118461130B_ABST
Patent Text Reader

Abstract

The invention discloses a polycrystalline composite tantalum carbide coating and a preparation method thereof, comprising the following steps: preparing a porous carbide coating on a clean substrate; cleaning and drying the porous carbide coating, mixing an inorganic tantalum salt, an alkane and hydrogen in a molar ratio of 2-5:2-5:1-2 in an inert atmosphere with argon as a carrier gas, and performing CVI deposition, wherein the pressure of the mixed gas is 5-100 mbar, the deposition temperature is 1000-1800°C, and the deposition time is 10-20 h to obtain the polycrystalline composite tantalum carbide coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of semiconductor material preparation, and in particular relates to a polycrystalline composite tantalum carbide coating and a preparation method thereof. Background Art

[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.

[0003] The third generation of semiconductors represented by silicon carbide, gallium nitride, aluminum nitride, etc. have higher critical electric fields and wider bandgap widths, and have good application prospects in the fields of high-energy and high-frequency electronic devices. However, the growth environment of the third generation of semiconductors is characterized by high temperature (>2100℃) and strong corrosion. During the growth process, the raw materials decompose and sublimate, and the atmosphere corrodes the graphite thermal field material, resulting in changes in the temperature field, increased replacement frequency, and increased production costs. The graphite thermal field material is corroded, and the C atmosphere and other impurity elements it produces enter the crystal growth interface, causing defects and a decrease in crystal quality.

[0004] Tantalum carbide ceramics have the characteristics of high melting point (3880℃) and high chemical stability. Their corrosion resistance far exceeds that of conventional base materials such as graphite. They are a potential material for protecting graphite bases, such as preparing a dense tantalum carbide coating on the surface of the base.

[0005] At present, among the preparation methods of tantalum carbide coating, the coating obtained by chemical vapor deposition (CVD) has the best density and purity, and is the most commonly used preparation method. However, due to the high brittleness of tantalum carbide coating and the mismatch of thermal expansion coefficient with the substrate material, the coating prepared by conventional chemical vapor deposition is densely deposited on the substrate surface. In a high-temperature growth environment, with the increase of temperature, the thermal mismatch between the graphite substrate and the coating gradually increases, resulting in the generation of thermal stress between the two, which manifests itself in the form of cracks, and then provides a channel for the growth atmosphere to erode the graphite substrate. With this position as the initial erosion point, the graphite substrate is gradually corroded, resulting in complete separation between the coating and the substrate, and protection failure. The conventional CVD method has a slow growth rate and is expensive. Although it is the main preparation method at present, the cost issue will also affect its large-scale promotion and use in single crystal growth.

[0006] In order to effectively solve the problem that tantalum carbide coatings are prone to cracking, the inventors tried to prepare a porous carbide transition layer between the tantalum carbide coating and the substrate, and gelled the tantalum salt solution to prepare tantalum sol, and then dipped and pulled the substrate prepared with the porous carbide coating in the tantalum sol, and then sintered it at high temperature to prepare the tantalum carbide coating. Since the particle size of the tantalum sol is small, the tantalum sol can penetrate a certain depth in the porous carbide coating during the immersion process. During the high-temperature sintering process, within a certain depth range, the formed tantalum carbide can fill the pores of the porous carbide coating to obtain a secondary dense protective layer, which can effectively improve the protective effect of the tantalum carbide coating while allowing the stress of the tantalum carbide coating to be better released.

[0007] However, the inventors found in experiments that although the sol-gel method can achieve good results, the penetration depth of tantalum sol in the porous carbide coating is limited (multiple immersion and drying treatments are required on the carbide coating to form a surface layer with a certain density, and the treatment process is complicated; and the stress release of tantalum carbide is limited. The composite substrate is prone to cracks after repeated use. Moreover, since the thickness of the secondary dense protective layer is relatively thin, the cracks of tantalum carbide are also prone to extend and penetrate the secondary dense protective layer as the number of uses increases, making the protection of the composite substrate ineffective. Summary of the invention

[0008] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a polycrystalline composite tantalum carbide coating and a preparation method thereof, which effectively solves the problem that the tantalum carbide coating products prepared by the conventional CVD method cannot be used for a long time and multiple times during the growth of silicon carbide single crystals. The thickness of the coating is mainly determined by the thickness of the porous carbide coating. It is only necessary to grow the TaC coating by the CVI method on the surface, which can effectively accelerate the growth rate of the coating and reduce its production cost. It can also extend the protection time during the single crystal growth process and reduce the single crystal growth cost. The slow growth rate of the chemical vapor deposition method is solved, the stress between the substrate and the coating is reduced, and the probability of crack formation is reduced.

[0009] In order to achieve the above object, the present invention is implemented through the following technical solutions:

[0010] In a first aspect, the present invention provides a method for preparing a polycrystalline composite tantalum carbide coating, comprising the following steps:

[0011] preparing porous carbide coatings on clean substrates;

[0012] After the porous carbide coating is cleaned and dried, in an inert atmosphere, an inorganic tantalum salt, an alkane and hydrogen are mixed in a molar ratio of 2-5:2-5:1-2 with argon as a carrier gas, and CVI deposition is performed. The pressure of the mixed gas is 5-100 mbar, the deposition temperature is 1000-1800°C, and the deposition time is 10-20 hours.

[0013] Chemical vapor infiltration (CVI) refers to a method of densifying the material by decomposing and polycondensing one or more hydrocarbon gas compounds at high temperatures to deposit carbon inside a porous medium.

[0014] In the present invention, an inorganic tantalum salt carried by an inert gas as a carrier gas is mixed with an alkane and hydrogen. During the high-temperature deposition process, the mixed gas penetrates into the porous carbide coating, and generates tantalum carbide deposited in the gaps of the porous carbide, so that the porous carbide layer is also more compact, and a tantalum carbide compact layer is formed on the surface of the porous carbide layer. Since the permeability of the mixed gas is very strong, it can basically penetrate to the junction of the porous carbide layer and the substrate, and the closer to the surface of the porous carbide layer, the more tantalum carbide is deposited, so that the compactness of the porous carbide after the deposition of tantalum carbide increases from the inside (the side close to the substrate) to the outside. The inventor has found through experiments that the stress buffer layer of this structure has better stress release performance, can effectively avoid the generation of cracks in the surface tantalum carbide compact layer, and the cracks generated are generally fine cracks existing inside the tantalum carbide, which will not extend to the surface of the tantalum carbide, and will not form through cracks.

[0015] In addition, since the stress buffer layer is thick, even if cracks occur in the surface tantalum carbide dense layer, the cracks are not easy to penetrate the stress buffer layer. Therefore, the composite substrate has a better protective effect on the substrate, so that the composite substrate can be reused multiple times or used continuously for a long time.

[0016] In some embodiments, the alkane is selected from one or a mixture of two or three of methane, ethane or propane.

[0017] In some embodiments, the heating rate during CVI deposition is 5-15° C. / min.

[0018] In some embodiments, the inorganic tantalum salt is selected from tantalum pentachloride.

[0019] In some embodiments, the evaporation temperature of the inorganic tantalum salt is 180-600°C.

[0020] Preferably, the flow rate of the carrier gas of the inorganic tantalum salt is 500-1000 sccm, the flow rate of the alkane is 50-200 sccm, and the flow rate of the alkane carrier gas is 500-2000 sccm.

[0021] In some embodiments, the porous carbide coating is prepared by uniformly coating a suspension formed by mixing carbide particles, a binder and a solvent in proportion, or uniformly coating a suspension formed by mixing a metal element, carbon powder, a binder and a solvent in proportion on the surface of a substrate; after drying, vacuum sintering at 1100-2500°C for 2-48h to obtain the coating.

[0022] Preferably, a sintering aid is added during the preparation of the porous carbide coating.

[0023] Preferably, the carbide is selected from one or a combination of WC, TiC or HfC; and the particle size is 0.11-10 μm.

[0024] Preferably, the metal element is selected from one or a combination of Ta, Ti, W or Nb; the particle size of the metal element and the carbon powder is 0.11-10 μm; the molar ratio of the metal element to the carbon powder is 1:0.8-1.2. The properties of the above carbides or carbides formed by the metal element and the carbon powder are similar to those of tantalum carbide, the thermal expansion coefficient is similar, and both have high temperature resistance, further reducing the probability of cracks in the dense tantalum carbide coating.

[0025] Preferably, the binder is selected from one or a combination of epoxy resin, silicone resin, graphite glue, phenolic resin, polyvinyl alcohol, polyurethane, acrylate or polyvinyl chloride.

[0026] Preferably, the solvent is selected from one or a combination of deionized water, trichloroethylene, toluene, styrene, benzene, anhydrous ethanol, chloroform, acetone, triethanolamine or ethyl acetate.

[0027] Preferably, in the suspension, the mass percentage of the carbide or metal element and graphite mixed powder is 50-80%, and the mass percentage of the binder is 1%-20%.

[0028] The suspension also includes a sintering aid, and the mass percentage of the sintering aid is 1%-20%.

[0029] In a second aspect, the present invention provides a polycrystalline composite tantalum carbide coating, which is prepared by the preparation method, and includes a tantalum carbide dense layer and a porous carbide and tantalum carbide composite layer, wherein the thickness of the tantalum carbide dense layer is 10-20 μm, and the thickness of the porous carbide and tantalum carbide composite layer is 50-200 μm.

[0030] In a third aspect, the present invention provides a composite substrate for preparing semiconductor materials, comprising a substrate and the polycrystalline composite tantalum carbide coating, wherein the polycrystalline composite tantalum carbide coating is attached to the surface of the substrate.

[0031] In some embodiments, the substrate is selected from graphite, C / C composites, ceramics, or metals.

[0032] The beneficial effects achieved by one or more embodiments of the present invention are as follows:

[0033] The present invention adopts tantalum carbide coating prepared by slurry sintering and CVI method, and the tantalum carbide particle layer is deposited on the surface of the substrate to form a loose stress buffer layer with a certain porosity, which can effectively reduce the thermal mismatch between the coating and the substrate material. CVI method deposition is carried out thereon to effectively fill the pores, and a densely packed layer is formed on the surface to block the growth cavity and graphite accessories, and reduce the erosion of the substrate by the growth atmosphere during the growth of silicon carbide single crystals. The method uses graphite and other materials as the substrate, applies the configured solution to the surface of the substrate for sintering, forms a first buffer layer, and then deposits the substrate surface by CVI technology to form a densely packed protective layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0035] Figure 1 It is a schematic cross-sectional view of a tantalum carbide coating prepared by a composite method of a slurry sintering method and a CVI method in Example 1 of the present invention;

[0036] Figure 2 This is a surface morphology of the tantalum carbide coating prepared by the slurry sintering method and the CVI method in Example 1 of the present invention.

[0037] Figure 3 This is a surface morphology of the tantalum carbide coating after silicon carbide single crystal growth in Example 1 of the present invention. DETAILED DESCRIPTION

[0038] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0039] The present invention will be further described below in conjunction with the embodiments.

[0040] Example 1

[0041] A high-purity graphite sheet was selected as the substrate material. The substrate had a diameter of 50 mm and a thickness of 10 mm. The sheet was placed in anhydrous ethanol for ultrasonic treatment for 5 min, then placed in deionized water for ultrasonic treatment for 5 min, and then dried by purging with nitrogen.

[0042] Weigh 25g of TiC powder (particle size 0.11-10μm), 1g of WC powder (particle size 0.11-10μm), 20ml of anhydrous ethanol, and 2g of epoxy resin, mix and stir, ultrasonicate for 5min to obtain a suspension, and let it stand for use. The suspension is evenly coated on the surface of the graphite substrate, and then placed in an oven to dry for 10h, and then placed in a vacuum environment and dried at 200°C for 10h.

[0043] The dried graphite substrate with the coating is sintered in vacuum at a temperature of 1800° C. for 2 hours. After sintering, it is naturally cooled to obtain a porous carbide coating with uniform thickness.

[0044] Place the sintered substrate material in the CVD reaction chamber, turn on the mechanical pump, pump the pressure in the chamber to below 10Pa, and turn on the molecular pump. When the pressure reaches a certain level, introduce inert gas argon as a carrier gas, pressurize to 50mbar, and then heat the reaction chamber to 1500℃.

[0045] The tantalum pentachloride evaporation chamber was heated to 300°C and maintained for 30 minutes. The carrier gas argon flow rate was 1000sccm, and it was transported to the reaction chamber. Methane (argon as carrier gas) and hydrogen (argon as carrier gas) were introduced simultaneously, wherein the tantalum pentachloride carrier gas argon flow rate was 1000sccm, the methane carrier gas argon flow rate was 1000sccm, the methane flow rate was 500sccm, and the hydrogen flow rate was 250sccm. The tantalum pentachloride flow rate was adjusted by its carrier gas flow rate and the room temperature of the evaporation chamber. After the gas was evenly mixed in the reaction chamber, it was deposited on the porous carbide coating for 10 hours to obtain a polycrystalline tantalum carbide coating.

[0046] Turn off the heating power supply and wait for the vapor deposition equipment to cool down; when the temperature drops below 50°C, turn on the vacuum pump to discharge the gas in the reaction chamber into the tail gas treatment device until the vacuum degree is below 100 Pa, then turn off the vacuum pump and let in argon gas. After the pressure in the reaction chamber rises to normal pressure, open the reaction chamber and take out the prepared graphite sheet composite substrate with multi-layer tantalum carbide coating.

[0047] The prepared tantalum carbide coated graphite material was characterized using scanning electron microscopy. Figure 1 This is a schematic cross-sectional view of a tantalum carbide coating prepared by a composite of a slurry sintering method and a CVI method in an embodiment, 100 is a substrate material, 200 is a carbide coating formed by a slurry sintering method, and 300 is a dense tantalum carbide coating obtained by a CVI method. Figure 2 The surface morphology of the tantalum carbide coating prepared by the slurry sintering method and the CVI method in the embodiment shows that the surface morphology of the coating is clear and free of impurities, and is not easily corroded, thereby ensuring the useful life of the coating.

[0048] Performance Testing:

[0049] The composite substrate prepared in this example was placed in a CVD reaction chamber, the mechanical pump was turned on to pump the pressure in the chamber to below 10 Pa, the molecular pump was turned on, argon was introduced to 50 mbar, and the reaction chamber was heated to 2350°C.

[0050] Methane and dichlorosilane were introduced with argon as carrier gas, with the methane carrier gas argon flow rate of 1000 sccm and the methane flow rate of 500 sccm; the dichlorosilane carrier gas flow rate of 1000 sccm and the dichlorosilane flow rate of 500 sccm. The gases were mixed evenly in the reaction chamber and deposited on the composite substrate for 200 hours to obtain silicon carbide single crystals.

[0051] Repeat the above silicon carbide single crystal preparation steps 6 times, Figure 3 This is the final surface morphology of the tantalum carbide coating. It can be seen that although it has been reused six times, the surface of the tantalum carbide is still dense and free of cracks. The quality of the prepared silicon carbide single crystal is also guaranteed.

[0052] Example 2

[0053] A high-purity graphite sheet was selected as the substrate material. The substrate had a diameter of 50 mm and a thickness of 10 mm. The sheet was placed in anhydrous ethanol for ultrasonic treatment for 5 min, then placed in deionized water for ultrasonic treatment for 5 min, and then dried by purging with nitrogen.

[0054] Weigh 26g of HfC powder (particle size 0.11-10μm), 2g of Ta powder and C powder mixture (the molar ratio of Ta powder to C powder is 1:1), 2g of phenolic resin, and 20ml of acetone, mix and stir, ultrasonicate for 5min to obtain a suspension, and let it stand for use. The coating suspension is evenly coated on the surface of the graphite substrate, and then placed in an oven to dry for 10h, and then placed in a vacuum environment to dry at 200°C for 10h.

[0055] The dried graphite substrate with the coating is sintered in vacuum at a temperature of 2000° C. for 10 hours. After sintering, it is naturally cooled to obtain a porous carbide coating with uniform thickness.

[0056] Place the sintered substrate material in the CVD reaction chamber, turn on the mechanical pump, pump the pressure in the chamber to below 10Pa, and turn on the molecular pump. When the pressure reaches a certain level, introduce inert gas argon as a carrier gas, pressurize to 50mbar, and then heat the reaction chamber to 1800℃.

[0057] The tantalum pentachloride evaporation chamber was heated to 300°C and maintained for 30 minutes. The carrier gas argon flow rate was 800 sccm, and it was transported to the reaction chamber. Methane (with argon as carrier gas) and hydrogen (with argon as carrier gas) were introduced simultaneously. The tantalum pentachloride carrier gas argon flow rate was 800 sccm, the methane carrier gas argon flow rate was 1000 sccm, the methane flow rate was 500 sccm, and the hydrogen flow rate was 250 sccm. The tantalum pentachloride flow rate was adjusted by its carrier gas flow rate and the temperature of the evaporation chamber. After the gas was evenly mixed in the reaction chamber, it was deposited on the porous carbide coating for 10 hours to obtain a multilayer polycrystalline tantalum carbide coating.

[0058] Turn off the heating power supply and wait for the vapor deposition equipment to cool down; when the temperature drops below 50°C, turn on the vacuum pump to discharge the gas in the reaction chamber into the tail gas treatment device until the vacuum degree is below 100 Pa, then turn off the vacuum pump and let in argon gas. After the pressure in the reaction chamber rises to normal pressure, open the reaction chamber and take out the prepared graphite sheet composite substrate with multi-layer tantalum carbide coating.

[0059] According to the performance testing method of Example 1, after the prepared composite substrate was reused for 5 times, no cracks were generated on the surface of the dense tantalum carbide coating.

[0060] Example 3

[0061] A high-purity graphite sheet was selected as the substrate material. The substrate had a diameter of 50 mm and a thickness of 10 mm. The sheet was placed in anhydrous ethanol for ultrasonic treatment for 5 min, then placed in deionized water for ultrasonic treatment for 5 min, and then dried by purging with nitrogen.

[0062] Weigh 28g of a mixture of Ti powder and carbon powder (the molar ratio of Ti powder to carbon powder is 1:1), 5g of graphite glue, and 15ml of deionized water, mix and stir, ultrasonicate for 5min to obtain a coating suspension, and let it stand for use. Use a spraying device to evenly coat the coating suspension on the surface of the graphite substrate. Place the coated graphite substrate in an oven and dry it for 10h, then place it in a vacuum environment and dry it at 200°C for 10h.

[0063] The dried graphite substrate with the coating is sintered in vacuum at a temperature of 2000° C. for 10 hours. After sintering, it is naturally cooled to obtain a porous carbide coating with uniform thickness.

[0064] Place the sintered substrate material in the CVD reaction chamber, turn on the mechanical pump, pump the pressure in the chamber to below 10Pa, and turn on the molecular pump. When the pressure reaches a certain level, introduce inert gas argon as a carrier gas, pressurize to 50mbar, and then heat the reaction chamber to 1800℃.

[0065] The tantalum pentachloride evaporation chamber was heated to 300°C and maintained for 30 minutes. The carrier gas argon flow rate was 800 sccm, and it was transported to the reaction chamber. Methane (argon was used as a carrier gas) and hydrogen (argon was used as a carrier gas) were introduced simultaneously. The tantalum pentachloride carrier gas argon flow rate was 800 sccm, the methane carrier gas argon flow rate was 1000 sccm, the methane flow rate was 500 sccm, and the hydrogen flow rate was 250 sccm. The tantalum pentachloride flow rate was adjusted by its carrier gas flow rate and the temperature of the evaporation chamber. After the gas was evenly mixed in the reaction chamber, it was deposited on the porous carbide coating for 10 hours to obtain a polycrystalline tantalum carbide coating.

[0066] Turn off the heating power supply and wait for the vapor deposition equipment to cool down; when the temperature drops below 50°C, turn on the vacuum pump to discharge the gas in the reaction chamber into the tail gas treatment device until the vacuum degree is below 100 Pa, then turn off the vacuum pump and let in argon gas. After the pressure in the reaction chamber rises to normal pressure, open the reaction chamber and take out the prepared graphite sheet composite substrate with multi-layer tantalum carbide coating.

[0067] According to the performance testing method of Example 1, after the prepared composite substrate was reused for 6 times, no cracks were generated on the surface of the dense tantalum carbide coating.

[0068] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a polycrystalline composite tantalum carbide coating, characterized in that: The steps include: preparing porous carbide coatings on clean substrates; After the porous carbide coating is cleaned and dried, in an inert atmosphere, an inorganic tantalum salt, an alkane and hydrogen are mixed in a molar ratio of 2-5:2-5:1-2 using argon as a carrier gas, and CVI deposition is performed, the pressure of the mixed gas is 5-100 mbar, the deposition temperature is 1000-1800°C, and the deposition time is 10-20 hours, thereby obtaining the obtained product; during the high-temperature deposition process, the mixed gas penetrates into the porous carbide coating to the junction between the porous carbide layer and the substrate, and generates tantalum carbide deposited in the voids of the porous carbide, making the porous carbide layer more dense, and forming a dense tantalum carbide layer on the surface of the porous carbide layer, and the closer to the surface of the porous carbide layer, the more tantalum carbide is deposited, so that the density of the porous carbide after the tantalum carbide is deposited increases from the side close to the substrate to the outside; The heating rate during CVI deposition is 5-15°C / min; the carrier gas flow rate of the inorganic tantalum salt is 500-1000sccm, the alkane flow rate is 50-200sccm, and the alkane carrier gas flow rate is 500-2000sccm; The inorganic tantalum salt is selected from tantalum pentachloride; The preparation method of the porous carbide coating is: A suspension formed by mixing metal element, carbon powder, sintering aid, binder and solvent in proportion is evenly coated on the surface of the substrate; after drying, it is vacuum sintered at 1100-2500°C for 2-48h to obtain; The metal element is Ta, Ti, W or Nb; In the suspension, the mass percentage of the metal element and the graphite mixed powder is 50-80%, and the mass percentage of the binder is 1%-20%.

2. The method for preparing a polycrystalline composite tantalum carbide coating according to claim 1, characterized in that: The alkane is selected from one or a mixture of two or three of methane, ethane or propane.

3. The method for preparing a polycrystalline composite tantalum carbide coating according to claim 1, characterized in that: The evaporation temperature of the inorganic tantalum salt is 180-600°C.

4. The method for preparing a polycrystalline composite tantalum carbide coating according to claim 1, characterized in that: The particle size of the metal element and the carbon powder is 0.11-10 μm.

5. The method for preparing a polycrystalline composite tantalum carbide coating according to claim 1, characterized in that: The binder is selected from one or a combination of epoxy resin, silicone resin, graphite glue, phenolic resin, polyvinyl alcohol, polyurethane, acrylate or polyvinyl chloride.

6. The method for preparing a polycrystalline composite tantalum carbide coating according to claim 1, characterized in that: The solvent is selected from one or a combination of deionized water, trichloroethylene, toluene, styrene, benzene, anhydrous ethanol, chloroform, acetone, triethanolamine or ethyl acetate.

7. A polycrystalline composite tantalum carbide coating, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 6, comprising a dense tantalum carbide layer and a composite layer of porous carbide and tantalum carbide, wherein the thickness of the dense tantalum carbide layer is 10-20 μm, and the thickness of the composite layer of porous carbide and tantalum carbide is 50-200 μm.

8. A composite substrate for preparing semiconductor materials, characterized in that: The invention comprises a substrate and the polycrystalline composite tantalum carbide coating according to claim 7, wherein the polycrystalline composite tantalum carbide coating is attached to the surface of the substrate.

9. The composite substrate for preparing semiconductor materials according to claim 8, characterized in that: The substrate is selected from graphite, C / C composite material, ceramic or metal.

Citation Information

Patent Citations

  • Tantalum carbide coating based on porous carbon material and preparation method thereof

    CN111825478A

  • Preparation method of SiC-Hf(Ta)C composite coating, composite coating and graphite base

    CN112391606A

  • Tantalum carbide coating formed on carbon-based surface as well as forming method and application of tantalum carbide coating

    CN112830815A

Cited By

  • A porous graphite-based tantalum carbide coating ceramic piece and a method of making the same

    CN122879672A